An Incomplete Psychological Novel: a Psychoanalytical Analysis of Hazel Lancaster in John Green’s The Fault in Our Stars - Pangestu, Nathania Astria; Sunardi, F.X. Dono (Journal of Language and Literature, 2016)
This paper is a psychoanalytical analysis of John Green’s The Fault in Our Stars (2012), aiming at identifying Hazel Grace Lancaster’s, the main character of the novel, self defense mechanisms and core issues as well as their potential causes. In so doing, this paper employs psychoanalysis theory by Sigmund Freud as its analytical tool. As a literary research, it uses a descriptive qualitative method, where we read the novel thoroughly, focused on the character and characterization of Hazel Grace and compared and analyzed it along with the theories that are used. The finding of this research is that this novel does contain its main character’s self-defense mechanisms and core issues evidence. The potential cause of the self-defense mechanisms can also be inferred from the character’s development and childhood. And yet, since this novel does not provide any clue or evidence as to how the main character develop her cBerliore issues, we come to the conclusion that this novel is not a complete psychological novel. Keywords: psychoanalysis, self-defense mechanisms, core issues